Improving Teacher Creativity: The Role of Service Leadership, Empowerment, and Work Motivation - Titin Gustini; Sri Setyaningsih; Eka Suhardi (STAI Hubbulwathan Duri, 2025)
Teacher creativity is essential for fostering engaging and effective learning environments. However, many teachers face challenges in developing creativity due to limited leadership support, lack of empowerment, and insufficient work motivation. This study investigates how service leadership, empowerment, and work motivation contribute to improving teacher creativity in kindergarten-level education in Sukaraja District, Sukabumi Regency. This research employed a quantitative approach using path analysis and the SITOREM method. The population comprised 152 kindergarten teachers, of which 111 were selected using proportional random sampling. Data were collected through a structured questionnaire measuring four variables: service leadership, empowerment, work motivation, and teacher creativity. Data were analyzed to determine both direct and indirect effects among the variables. Findings show that service leadership (β = 0.302), empowerment (β = 0.239), and work motivation (β = 0.194) have significant direct positive effects on teacher creativity. Service leadership (β = 0.234) and empowerment (β = 0.302) also positively affect work motivation. However, indirect effects of leadership and empowerment on creativity through motivation were statistically insignificant based on the Sobel test (p 0.05). The results indicate that improving teacher creativity requires strengthening leadership practices, providing empowering environments, and enhancing intrinsic motivation. While motivation serves as a contributing factor, it does not mediate the relationship significantly. Future research should explore other mediators or moderators that may better explain this linkage.